Struktura obiektów kosztowych a hierarchia działań - Putyra, Adam (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Activity based costing was introduced to overcome numerous shortcomings of traditional costing systems. In order to achieve that not only did it state activities as the core causes of incurring costs but also it pointed out that products are not the only cost objects of the company. ABC puts an accent on the cause and effect relation at each stage of allocating indirect costs. It distinguishes many levels of activities in order to trace the costs of activities directly to cost objects that benefit from these activities. Activities as well as cost objects are therefore set in hierarchical structures. The paper presents the development of cost objects structures reflecting changes appeared in business environment. It also describes two approaches to cost flow existence within these structures. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1178, s. 134-146